William of Malmesbury - Thomson, Rodney M. 1946- (The Boydell Press, 2003)
This is the first book devoted entirely to William of Malmesbury, England's greatest historian after Bede, one of the great figures of the 12th-century renaissance. Although best known for his historical writings, William was also a biblical commentator, scribe and editor of texts. Here, R.M. Thomson looks at the man, his times and his work as a man of letters